2019
DOI: 10.1021/acs.orglett.9b02705
|View full text |Cite
|
Sign up to set email alerts
|

Calcium(II)- and Triflimide-Catalyzed Intramolecular Hydroacyloxylation of Unactivated Alkenes in Hexafluoroisopropanol

Abstract: We report an efficient intramolecular hydroacyloxylation of unactivated alkenes, offering a streamlined access to relevant γ-lactones, which features the utilization of either a calcium(II) salt or triflimide as a catalyst in hexafluoroisopropanol. This method could be applied to the synthesis of natural products and the late-stage functionalization of natural and bioactive molecules. Additionally, DFT computations were used to elucidate the twist of reactivity observed between the hydroamidation and hydroacyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 57 publications
0
24
1
Order By: Relevance
“…particularly effective to yield the desired compounds from unsaturated carboxylic acids (Scheme 29). 50 This method could be applied to the synthesis of natural products and to the postfunctionalization of natural and bioactive compounds. However, in the presence of an electron-withdrawing group (EWG) in the position of the carboxylic acid, the reaction had to be performed with HNTf2 as a catalyst.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…particularly effective to yield the desired compounds from unsaturated carboxylic acids (Scheme 29). 50 This method could be applied to the synthesis of natural products and to the postfunctionalization of natural and bioactive compounds. However, in the presence of an electron-withdrawing group (EWG) in the position of the carboxylic acid, the reaction had to be performed with HNTf2 as a catalyst.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…In the past years, HFIP has become a prominent solvent in organic synthesis due to its combination of atypical properties, including strong H-bond donating ability, low nucleophilicity, redox stability, and mild acidity . It allowed us to achieve reactions that were unlikely to take place in traditional organic solvents, ,, emphasizing that, when HFIP was associated with a Lewis acid or a Brønsted acid, the acidity of the corresponding combination could be considerably boosted to even activate unreactive substrates such as highly deactivated styrenes. Recently, we applied this principle to the ortho -C alkylation of anilines with alkenes, which relies on a concerted-like mechanism that is fostered by the presence of HFIP and prevents common regioselectivity issues associated with this type of process (Scheme c).…”
mentioning
confidence: 99%
“…Mechanistic studies further revealed that the introduction of hexafluoroisopropanol (HFIP) [9] could dramatically increase the acidity of the system via the formation of H‐bonding interactions with Ca(NTf 2 ) 2 , thereby facilitating the subsequent transformations even with highly electronically deactivated substrates [10] . By virtue of the established calcium catalysis, a variety of challenging transformations such as arylation, [10d,e] aza‐Piancatelli reaction, [10a,f] hydroacyloxylation, [10c] hydroamidation [10b] have been well addressed thus far. With our efforts, more recently we have also developed an ortho ‐C‐alkenylation/hydroacyloxylation sequence to assembly phthalides benefit from this Ca(NTf 2 ) 2 /HFIP co‐catalytic system [10h] .…”
Section: Introductionmentioning
confidence: 99%